MORTALITAS LALAT MUSCA DOMESTICA YANG DIBERI ESKTRAK METANOL CHROMOLAENA ODORATA - Gerson Y. I. Sakan; Ni Sri Yuliani; Yosefus F. da Lopez; I Gusti Komang Oka Wirawan (Partner, 2023)
This study aimed the methanol extract of the leaves of Chromolaena odorata against Musca domestica flies. The research design used a completely randomized design with 4 treatments with 5 replications. Each experimental unit contained 20 flies. The tested extracts were divided into concentrations of 10% (P1), 20% (P2), 30% (P3), and 10% soap solution was applied by spray. The variables observed were flies that died after 12 hours of exposure to the extract. The data obtained was tested with ANOVA, if there was a significant difference, it was continued with the Duncan test. Based on the statistical results showed that there was a very significant difference between treatments (P<0.01). Duncan's test showed there was a significant difference in mortality of P4 with mortality of P1, P2, and P3 where P1, P2, and P3 gave the same effect on mortality of flies 89-100%. Thus the concentration of P1, P2, and P3 is better.Key Words:  Mortality, Musca domestica, Methanol extract, Chromolaena odorata